Small biodiversity effects on leaf litter production of a seasonal heath vegetation. (30th June 2020) - Silva, José Luiz Alves; Souza, Alexandre Fadigas; Santiago, Louis Stephen; Gripp, Anderson da Rocha; Asato, Ana Elizabeth Bonato; Silva, Gabriel Henrique Santos; Alencar, Mery Ingrid Guimarães de; Caliman, Adriano
Abstract: Aims: We evaluated the relative importance that biodiversity factors, abiotic conditions, and vegetation structure have on monthly leaf litter production. We tested if biodiversity drives leaf litter production through the increase in species richness or community‐weighted mean traits regardless of the influence of other biodiversity factors that reflect species niche differentiation, such as phylogenetic and functional diversities. We also tested if precipitation imposes greater influence on the production than any asynchronous effects between species that result from temporal niche partitioning. Location: Seasonal heath vegetation that covers white‐sand coastal areas in northeastern Brazil. Methods: We conducted an observational study across 41 25‐m 2 permanent plots to sample leaf litter production of the vegetation during 18 months from January 2016 to June 2017 at monthly intervals. We used structural equation modeling in combination with linear mixed models to test the above‐mentioned hypotheses. Results: Our study encompassed 22 focal species. Species richness was the only biodiversity factor to influence leaf litter production, although its effect was weak, suggesting that the chance of including high‐yielding species by increasing richness enhances the production regardless of the degree of species niche complementarity through functional and phylogenetical dissimilarities. We also observed a major control of precipitation on leaf litter production, as well as a lack of interaction between species richness and its temporal dynamic of production, demonstrating the key role of climate‐mediated controls. Conclusion: We believe that plant diversity loses importance for ecosystem functioning in ecological contexts where the entire community responds similarly to abiotic pressures, particularly if the ecosystem process is marked by strong temporal dynamics. Our study provided empirical support for this line of reasoning since the seasonal heath vegetation responded mostly to rainfall seasonality. Abstract : Leaf litter production was promoted by few dominant species that enhance the overall production wherever they occur with little or no effect of species niche differentiation. Precipitation seasonality imposed greater influence on leaf litter production than any asynchronous effect between species, as asynchrony can result from temporal niche partitioning, which demonstrates the key role of climate‐mediated controls.